Erdheim-Chester disease and slowly progressive cerebellar dysfunction. Issue 2 (February 1995) - Fukazawa, T; Tsukishima, E; Sasaki, H; Hamada, K; Hamada, T; Tashiro, K
Abstract : A 59 year old woman developed pronounced thirst, increased water intake, and increased urinary output followed by slowly progressive cerebellar symptoms. Brain MRI showed abnormal hyperintensity on T2 weighted studies in the region of both dentate nuclei without atrophy of the cerebellum or the brainstem. A 99mTC diphosphonate bone scan showed bone lesions in the distal parts of both femurs as well as distal and proximal parts of both tibias. The diagnosis of Erdheim-Chester disease was made by bone biopsy. This is the first case of Erdheim-Chester disease presenting as a slowly progressive cerebellar syndrome and diabetes insipidus, and also showing high signal lesions in deep cerebellar nuclei on MRI. Skeletal surveys are indicated for patients with otherwise unexplained slowly progressive cerebellar symptoms.